Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik CV. Aurelia Weida Prima Medan Dengan Metode Maut - Imam Saputra; Rizalun Nafsi Siregar (STMIK Budi Darma, 2022)
Choosing top employees is a company appreciation for their performance. This can motivate employees to be more motivated at work. To obtain the best employee names, a system that does the expected selection process and can produce objective, transparent information. Company CV. Aurelia weida is prime field in search of the best employees, the company does this by pointing out without adequate good judgment. Therefore, a decision-making system is needed in evaluating employee performance. This research USES a multi-applied theory method. The data prepared for this evaluation is 10 samples from CVS. Aurelia weida is prime field. Assessments are based on some criteria and weights given. There are 6 data criteria for judging a employee's performance, which is service (weight 30%), integrity (weight 20%), commitment (weight 15%), discipline (weight 20%), cooperation (weight 13%), employee performance (weight 12%). Calculations were obtained by employees who had the highest marks. Therefore, maximum value is obtained on alternative 3 with a value of 0.786, and minimum value is obtained on alternative 8 with a value of 0.369. It's coming up for CV after all. The aurelia weida prime field evaluates its employees over a period of time. It turned out that the best employee performance ever helped CV. Aurelia weida is prime field